2015
DOI: 10.1111/1346-8138.13019
|View full text |Cite
|
Sign up to set email alerts
|

Novel splice site mutation in the fumarate hydratase (FH) gene is associated with multiple cutaneous leiomyomas in a Japanese patient

Abstract: Cutaneous leiomyoma is a benign skin tumor that originates from the smooth muscle, such as the arrector pili muscle of the hair follicles. Familial cases with multiple cutaneous leiomyomas exist, which typically show an autosomal dominant inheritance trait. Most patients with the disease are known to carry heterozygous germ line mutations in the fumarate hydratase (FH) gene and can be complicated by tumors in internal organs, especially uterine leiomyoma and renal cell cancer in high frequency. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(63 reference statements)
2
5
0
Order By: Relevance
“…Five previously reported Japanese families with HLRCC exhibited different mutations, including four missense mutations and a splice site mutation that have not been reported in Caucasian families. [11][12][13][14][15] These mutations together with the novel mutation pattern detected in the current case indicate the existence of several founders in Japan harboring FH mutations distinct from those detected in Caucasian families.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Five previously reported Japanese families with HLRCC exhibited different mutations, including four missense mutations and a splice site mutation that have not been reported in Caucasian families. [11][12][13][14][15] These mutations together with the novel mutation pattern detected in the current case indicate the existence of several founders in Japan harboring FH mutations distinct from those detected in Caucasian families.…”
Section: Discussionsupporting
confidence: 57%
“…Although the case did not meet the clinical diagnostic criteria of HLRCC, cumulative information of renal histopathology after the patient's death made us investigate the possibility of FH mutation. Five previously reported Japanese families with HLRCC exhibited different mutations, including four missense mutations and a splice site mutation that have not been reported in Caucasian families . These mutations together with the novel mutation pattern detected in the current case indicate the existence of several founders in Japan harboring FH mutations distinct from those detected in Caucasian families.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…FH is a homotetrameric protein present in two isoforms coded by the same gene, a mitochondrial isoform involved in the conversion of fumarate to malate in the TCA cycle, and a cytosolic isoform involved in amino acid catabolism and the urea cycle (Yogev et al , ). FH germline mutations, which are often missense mutations and are particularly frequent in exons 4, 5, 7 and 8 (Bayley, Launonen, & Tomlinson, ; Picaud et al , ; Yoshinaga et al , ), have been found to decrease FH activity with the consequent accumulation of fumarate. Decreased functionality of FH predisposes individuals to several pathologies including multiple cutaneous leiomyomas, uterine leiomyomas, and the familial syndrome hereditary leiomyomatosis and renal cell cancer (HLRCC), which causes smooth muscle tumours and renal cell carcinomas (Bayley et al , ; Ha et al , ).…”
Section: Oncometabolites and Their Related Metabolic Enzymesmentioning
confidence: 99%
“…Most clinically relevant missense mutations affect residues that are evolutionarily conserved [ 39 , 40 ]. Other mutations, such as deletions or splice-site mutations, often result in omission of whole segments of the protein and thus cause severe disruptions in conformation of the protein [ 25 , 41 , 42 ]. Overall, mutations in FH seem to cause structural changes to the enzyme that eliminate or compromise enzymatic function.…”
Section: Introductionmentioning
confidence: 99%